Operational amplifiers : theory and design - Huijsing, Johan H., 1938- (Springer, 2016)
This new edition contains state-of-the-art material as well as the essentials. It includes a systematic approach to the design of chopper and auto-zero OpAmps and Instrumentation Amplifiers with input offset voltages of the order of 1uV.- Resumé vydavatel
Keywords: operační zesilovače; operational amplifiers; elektronické knihy; učebnice vysokých škol; electronic books; textbooks (higher)